Autocrine TGF-β1/miR-200s/miR-221/DNMT3B regulatory loop maintains CAF status to fuel breast cancer cell proliferation. (28th June 2019) - Tang, Xi; Tu, Gang; Yang, Guanglun; Wang, Xing; Kang, Linmin; Yang, Liping; Zeng, Huan; Wan, Xueying; Qiao, Yina; Cui, Xiaojiang; Liu, Manran; Hou, Yixuan
Abstract: Cancer-associated fibroblasts (CAFs) remain active even in the absence of cancer cells. However, the molecular mechanism underlying the sustained active status of CAFs is largely unrevealed. We found that in CAFs, DNMT3B was not only a target of miR-200b, miR-200c and miR-221, but was able to induce DNA methylation of miR-200s promoters. DNMT3B eventually reached a stably high level by the counteracting effect of decreasing miR-200b/c and increasing miR-221 in normal fibroblasts (NFs) with long-term exogenous TGF-β1 treatment, and DNMT3B further led to a low level of miR-200s which established CAF activation. Meanwhile, miR-200s/miR-221/DNMT3B signaling sustained autocrine TGF-β1 maintaining active CAF status. Destruction of the autocrine TGF-β1/miR-200s/miR-221/DNMT3B signaling led to demethylation of miR-200s promoters and further restored the NF phenotypes. Moreover, we confirmed that TCF12, the target of miR-141, stimulated c-Myc/Cyclin D1 axis in breast cancer cells to promote cancer growth by enhancing CXCL12 of CAFs. The current study reveals that the TGF-β1/miR-200s/miR-221/DNMT3B regulatory loop is responsible for the maintenance of CAFs status and is also necessary for CAF function in promoting malignance of breast cancer, which provides a potential target for CAF-driven therapeutic strategy. Highlights: In CAFs, DNMT3B is a direct target of miR-200b/c and miR-221, and could induce DNA methylation of miR-200s promoters. Increasing miR-221 counteracts decreasing miR-200b/c in regulating DNMT3B and autocrine TGF-b1 in the programming of CAFs. The autocrine TGF-b1/miR-200b/c/miR221/DNMT3B axis is maintained in a self-stimulating pattern. Autocrine TGF-b1/DNMT3B/miR-141 axis enhances TCF12/CXCL12 signaling in active CAFs to promote breast cancer proliferation.